Toward Long-Term Communication With the Brain in the Blind by Intracortical Stimulation: Challenges and Future Prospects - Fernández, Eduardo; Alfaro, Arantxa; González-López, Pablo (Frontiers in Neuroscience, 2020)
The restoration of a useful visual sense in a profoundly blind person by direct electrical stimulation of the visual cortex has been a subject of study for many years. However, the field of cortically based sight restoration has made few advances in the last decades and many problems remain. In this context, the scientific and technological problems associated with safe and effective communication with the brain are very complex and there are still many unresolved issues delaying its development. In this work, we review some of the biological and technical issues that still remain to be solved, including long-term biotolerability, the number of electrodes required to provide a useful vision and, the delivery of information to the implants. Furthermore, we emphasize the possible role of the neuroplastic changes that follow vision loss for the success of this approach. We propose that increased collaborations among clinicians, basic researchers and neural engineers will enhance our ability to send meaningful information to the brain and restore a limited but useful sense of vision to many blind individuals.